Work Context and Burnout syndrome in the nursing team of the Family Health Strategy - Renata Bernardes Lacerda; Maria Beatriz Guimarães Ferreira; Carolina Feliciana Bracarense; Lidiane Vieira de Sene; Ana Lúcia de Assis Simões (Universidad de Alicante, 2016)
Purpose: Investigate the relationship between the working conditions and the Burnout Syndrome of nursing professionals of Family Health Strategy town of Minas Gerais. Methods: Cross-sectional study with a quantitative approach. The study group was composed of 50 nursing professionals who answered the questionnaire of sociodemographic and professional, Work Context Assessment Scale (EACT) and Maslach Inventory Burnout. Exploratory and bivariate analyzes were used at 5% significance level. Results: The dimension Emotional Exhaustion was significantly correlated with all factors of EACT; Depersonalization presented diference with the Socio-professional Relations and Work Organization; Decreased Personal accomplishment correlated with Labour Organization. Conclusion: Worst are the conditions and organization of work and the socio-professional relations, the greater the possibility of dissatisfaction, development of nonchalance attitudes, disease and emotional exhaustion among nursing professionals in primary care.